Deep Inferior Epigastric Perforators Topography for “Island Transverse Rectus Abdominis Musculocutaneous Flap” in Breast Reconstruction - Kim, Tae Hyun; Jeong, Seong Heum; Ahn, Hee Chang (Archives of Plastic Surgery, 2023)
Background The Island transverse rectus abdominis musculocutaneous (TRAM) flap is well vascularized with very reliable blood flow, because all perforators of the zone I are included when it is harvested. The number of perforators, topographic mapping, and their relationship with reconstructed outcomes were investigated.Methods Fifty patients with Island TRAM breast reconstruction from September 2021 to August 2022 were investigated. The zone I was divided into a total of eight sections. Under the loupe magnification, all perforators larger than 0.5 mm in zone I were counted with fine dissection, and photographs were taken in background of vessel loops. Complications like flap necrosis, seroma, and hematoma were also investigated.Result There are 12 ideal perforators on average in zone I such as one perforator in section I, II, IV, V, VI, VIII, and three perforators in section III and VII. However, two perforators (M6 and L6) below arcuate line were sacrificed in the time of flap harvest to prevent hernia. Island TRAM included 10 perforators on average (5 perforators in each side) above arcuate line to be transferred to the recipient site. Only minor complications were identified.Conclusion The Island TRAM flap includes 10 perforators to get the vigorous blood flow. The periumbilical to upper medial perforators become more dominant in the perfusion of the flap after deep inferior epigastric artery division. Well preserved perforators will guarantee the satisfactory breast reconstruction with the least complication.
Keywords: perforators; Island TRAM flap; breast reconstruction; topographic mapping